On non-generic finite subgroups of exceptional algebraic groups - Litterick, Alastair J., 1986- (Memoirs of the American Mathematical Society ;, 2018)
The study of finite subgroups of a simple algebraic group G reduces in a sense to those which are almost simple. If an almost simple subgroup of G has a socle which is not isomorphic to a group of Lie type in the underlying characteristic of G, then the subgroup is called non-generic. This paper considers non-generic subgroups of simple algebraic groups of exceptional type in arbitrary characteristic.